Social and dialogic thinking and learning in special education : radical insights from a postcritical ethnography in a special school - Erickson, Karen A.; D'Ardenne, Charna; Clark, Nitasha M.; Koppenhaver, David, 1956-; Noblit, George W. (New York, NY : Routledge, 2022)
Drawing on a three-year post-critical ethnography, this volume counters deficit-based notions of disability to present a new social and dialogic theory of thinking and learning for students with significant support needs. Dismantling ideas around ableism/disableism, Social and Dialogic Thinking and Learning offers a uniquely theoretical and conceptual contribution to special education and capability research. Illustrating how students exhibit varied practical, social, and creative abilities, possess agency and perform identity, chapters present a challenge to the restrictive ways in which disability is constructed through prescriptive forms of teacher-student interaction and instruction. The text ultimately offers a powerful re-imagining of how educators and researchers can perceive, observe, and respond to students beyond current institutional and cultural norms. This text will benefit researchers, academics, and educators with an interest in inclusion and special educational needs, disability studies, and the theories of learning more broadly. Those specifically interested in educational psychology and the study of severe, profound, and multiple learning difficulties will also benefit from this book.
Keywords: EDUCATION / Special Education / General; EDUCATION / Multicultural Education; Special education -- Political aspects; Special education -- Social aspects